What motivates customers to purchase HONDA automobiles? - nadeka, lora Arista (ESENSI: Jurnal Manajemen Bisnis, 2024)
The purpose of this study is to use a brand image to ascertain how brand equity and awareness affect purchase decisions. Customers of Honda vehicles make up the population in this study. Purposive sampling, utilizing a sample size of 254 respondents overall, was the approach employed. Utilizing PLS version 3.0 software and structural equation modeling (SEM) to test the validity and reliability of a questionnaire given to respondents, the data-gathering approach makes use of this technique. Brand awareness has a favorable and considerable impact on brand image, but it does not affect purchasing decisions, according to the research results. Purchase decisions are positively and significantly impacted by brand equity, while brand image is positively and significantly impacted by brand equity. Purchasing decisions are positively and significantly impacted by brand image. The findings indicate that to raise brand recognition, Honda needs to be able to help prospective customers recognize, comprehend, and/or remember the Honda brand when utilizing its products.